2013
DOI: 10.1371/journal.pone.0079976
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Individual- to Population-Level Impacts of Disease on Coral Reef Sponges: Using Spatial Analysis to Assess the Fate, Dynamics, and Transmission of Aplysina Red Band Syndrome (ARBS)

Abstract: BackgroundMarine diseases are of increasing concern for coral reef ecosystems, but often their causes, dynamics and impacts are unknown. The current study investigated the epidemiology of Aplysina Red Band Syndrome (ARBS), a disease affecting the Caribbean sponge Aplysina cauliformis, at both the individual and population levels. The fates of marked healthy and ARBS-infected sponges were examined over the course of a year. Population-level impacts and transmission mechanisms of ARBS were investigated by monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 64 publications
(99 reference statements)
0
25
0
Order By: Relevance
“…Increased disintegration of the thylakoid membranes of S. spongiarum, which would decrease the concentration of photosynthetic pigments, was observed in ARBS‐affected tissues, and this observation supports previous work that found reduced concentrations of chlorophyll a in ARBS‐affected individuals of A. cauliformis (Gochfeld, Easson, et al, ). This reduction in photopigments likely affects the sponge, which derives nutrients from this association, and may help to explain the slower growth and reduced biomass previously reported for ARBS‐affected sponges (Easson et al, ; Gochfeld, Easson, et al, ; Gochfeld, Kamel, et al, ).…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…Increased disintegration of the thylakoid membranes of S. spongiarum, which would decrease the concentration of photosynthetic pigments, was observed in ARBS‐affected tissues, and this observation supports previous work that found reduced concentrations of chlorophyll a in ARBS‐affected individuals of A. cauliformis (Gochfeld, Easson, et al, ). This reduction in photopigments likely affects the sponge, which derives nutrients from this association, and may help to explain the slower growth and reduced biomass previously reported for ARBS‐affected sponges (Easson et al, ; Gochfeld, Easson, et al, ; Gochfeld, Kamel, et al, ).…”
Section: Discussionmentioning
confidence: 69%
“…To date, ARBS is the only Caribbean sponge disease shown to be readily transmissible (Olson et al, ). Long‐term monitoring of populations of A. cauliformis identified direct contact as the primary mode of disease transmission among these branching sponges (Easson et al, ), and this has been confirmed experimentally (Olson et al, ). Waterborne transmission occurs as well, although less rapidly (Easson et al, ; Olson et al, ).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations